Objective structured clinical examination in nursing education: a comprehensive review - N., Rajkannan; Mathew, Niky; N., Gowthami B.; R., Nandeesh Kumar P.; N., Deepu B.; N., Sahana I.; R., Madhusmitha (International Journal of Research in Medical Sciences, 2026)
The preparation of clinically competent nurses is a fundamental responsibility of nursing education systems worldwide. Conventional assessment approaches in nursing education frequently prioritize knowledge acquisition over integrated clinical performance, thereby providing an incomplete representation of a student’s readiness for real-world practice. As nursing roles expand in complexity and responsibility, assessment strategies must evaluate not only theoretical understanding but also the application of skills, clinical reasoning, communication, and professional behaviour. The Objective Structured Clinical Examination (OSCE) emerged as an assessment methodology designed to systematically evaluate the application of clinical knowledge, skills, and professional behaviours in controlled practice settings. This review examines the conceptual foundations, historical development, structural design, implementation strategies, educational impact, strengths, limitations, and future directions of OSCE in nursing education. Particular emphasis is placed on nursing-specific competencies such as psychomotor proficiency, clinical decision-making, communication, ethical practice, professionalism, and patient safety within competency-based curricula. Evidence from national and international literature supports OSCE as a valid and reliable assessment approach that enhances clinical preparedness, accountability, and professional confidence among nursing students.